Characterization and Water Uptake of Reinforced Polymer Blend Using Nanoclay and Rock Wool - Rana Salih; Shanaz Ahmad (Journal of Applied Sciences and Nanotechnology)
The current work focuses on assessing flexural properties, and water uptake of polymeric composites prepared using various reinforcements. These additives consist of kaolinite nano clays and rock wool (RW). In addition to a polymer blend that consists of epoxy and polyester resins as the matrix. The castings were made using a hand lay-up approach. Nanoclay (NC) was added in weight fractions of 5% and 7%, together with RW added in a volume fraction of 10% as reinforcement. The impact test was employed to decide the optimum mixing ratio of the polymer blend that used as a matrix. From the results the blend consisting of 80 wt.% epoxy and 20 wt.% polyester has the highest impact strength value. Thermal analysis was done using differential scanning calorimetry (DSC) as a characterization method to assess the miscibility of the polymer blend. The polyester/epoxy blend showed the maximum flexural strength, which determined as (57.4) MPa. While the hybrid reinforcement using NC (5 wt.%) and RW (10%) lowered the flexural strength to 16.53 MPa. From the water absorption test results showed that, in addition to the standard concentration, the type of material also affects water, in addition to the ratios of its components. Finally, DSC results revealed the presence of two different glass transition temperatures, which indicates that the epoxy/polyester blend is immiscible and there are two distinct phases in this matrix.